Temperature-dependent global gene expression in the Antarctic archaeon Methanococcoides burtonii - CAMPANARO, STEFANO; TREU, LAURA; WILLIAAMS TJ; BURG DW; DE FRANCISCI D; LAURO FM; CAVICCHIOLI R. (Environmental Microbiology, 2011)
Methanococcoides burtonii is a member of the Archaea that was isolated from Ace Lake in Antarctica and is a valuable model for studying cold adaptation. Low temperature transcriptional regulation of global gene expression, and the arrangement of transcriptional units in cold-adapted archaea has not been studied. We developed a microarray for determing which genes are expressed in operons, and which are differentially expressed at low (4°C) or high (23°C) temperature. Approximately 55% of genes were found to be arranged in operons that range in length from 2 to 23 genes, and mRNA abundance tended to increase with operon length. Analysing microarray data previously obtained by others for Halobacterium salinarum revealed a similar correlation between operon length and mRNA abundance, suggesting that operons may play a similar role more broadly in the Archaea. More than 500 genes were differentially expressed at levels up to ∼24-fold. A notable feature was the upregulation of genes involved in maintaining RNA in a state suitable for translation in the cold. Comparison between microarray experiments and results previously obtained using proteomics indicates that transcriptional regulation (rather than translation) is primarily responsible for controlling gene expression in M. burtonii. In addition, certain genes (e.g. involved in ribosome structure and methanogenesis) appear to be regulated post-transcriptionally. This is one of few experimental studies describing the genome-wide distribution and regulation of operons in archaea.